2014
DOI: 10.3341/kjo.2014.28.2.186
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Acute Anterior Uveitis and Optic Disc Edema Following a Snake Bite

Abstract: The authors wish to report a case of bilateral acute anterior uveitis and optic disc edema following a hemotoxic snake bite, in order to highlight the concomitant occurrence of these conditions and the potential adverse effects of anti-snake venom (ASV). A 35-year-old male was bitten by a viper at seventeen thirty hours, and was started on ASV. Two days following treatment he experienced sudden onset redness and painful diminution of vision in both eyes (OU). On examination, the patient's visual acuity (VA) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Steroids play a beneficial role in the management of these symptoms. 16 Rao in 1981 reported the immediate development of blindness after a cobra bite and recognized it to the lethal influence of the venom per se. 17 Mathur described a case of nonpoisonous snake bite that developed optic neuritis following administration of ASV.…”
Section: Discussionmentioning
confidence: 99%
“…Steroids play a beneficial role in the management of these symptoms. 16 Rao in 1981 reported the immediate development of blindness after a cobra bite and recognized it to the lethal influence of the venom per se. 17 Mathur described a case of nonpoisonous snake bite that developed optic neuritis following administration of ASV.…”
Section: Discussionmentioning
confidence: 99%
“…18 A similar case of anterior uveitis and optic disc edema following haematotoxic bite reported from South India was considered as an adverse effect of SAV or a direct toxic effect of the venom. 19 Their patient was treated with steroids and intra venous methyl prednisolone with visual improvement and resolution of disc edema. S Nayak et al had reported on uveitis following SAV in 2 patients.…”
Section: Discussionmentioning
confidence: 99%